Moral sovereigntism: A co-instantiation appraisal analysis of President Prabowo Subianto’s UN address - Nainggolan, Bernard Richard; Hutagalung, Erwin Efendi; Norawati, Rosinta (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2025)
The rise of “post-Western” political discourse presents a significant rhetorical puzzle: how do nationalist leaders perform sovereign strength while simultaneously adhering to the multilateral norms of institutions like the United Nations? This article investigates this “sovereigntist’s dilemma” through a case study of Indonesian President Prabowo Subianto’s 2025 UN General Assembly address. While previous research using Systemic Functional Linguistics (SFL) has analyzed Appraisal systems in isolation, this study argues that such fragmentation misses the functional unity of political rhetoric. Employing a rigorous “co-instantiation” methodology, we mapped the simultaneous bundling of evaluative resources across the speech (N=335). The findings reveal a dominant “rhetorical trialectic” comprising Attitude: Judgement (26.9%), Engagement: Contraction (23.9%), and Graduation: Force (21.5%). We argue that this specific configuration constructs a stance of “moral sovereigntism,” wherein the speaker co-opts the language of global morality to justify nationalist capacity. By reframing national strength not as a threat to multilateralism but as the only vehicle for achieving it, the speech resolves the ideological contradiction. This study contributes a replicable methodological protocol for analyzing the bundled nature of political stance.